APLICATION TECHNOLOGY NANOPARTICLES ON COSMETIC PREPARATION - IRMA RAHAYU LATARISSA; Patihul Husni (Fakultas Farmasi, Universitas Padjadjaran, 2016)
The development of nanoparticle technology increasingly rapid makes the application of these nanoparticles become more prevalent in the pharmaceutical industry especially cosmetic preparations Cosmetic is applied to the human body to cleanse, beautify or improve the attractiveness or the person's appearance. Nanoparticles are used for cosmetics various kinds such as Solid Lipid Nanoparticles (SLN, Nanostructured Lipid Carriers (NLS), nanoparticles of titanium oxide (TiO2) and zinc oxide (ZnO), silver nanoparticles, crystal nanoparticles, gold nanoparticles, and so on. Indications are given also an assortment that is as an antioxidant, antiaging, antiacne, to protect the skin from UV rays and improve penetration of the skin. Application of nanoparticles in cosmetic preparations intended to release cosmetic active ingredients is more targeted due to the small particle size and to reduce side effects.